The Effectiveness of SSCS Learning Model with KNWS Strategy towards Mathematical Creative Thinking Ability and Self Confidence of Students - Warda, Asa Kuntifatin; Mashuri, Mashuri; Amidi, Amidi (Department of Mathematics, Universitas Negeri Semarang, 2017)
Type of this study is quantitative. The purpose of this study was to determine the effectiveness of SSCS learning model with KNWS strategy towards mathematical creative thinking ability and self confidence of students. The populations of this study was students at grade VIII SMP Muhammadiyah 8 Semarang academic year 2016/2017. The sampling was done by cluster random sampling technique, which were chosen VIIIA as experiment class and VIIIC as control class. Data collection methods used documentation, a test, a questionnaire, and an observation. The result of this study stated that the mathematical creative thinking ability of the experiment class students had reached the classical completeness, percentage of mastery learning on mathematical creative thinking ability of the experiment class students was better than that percentage of the control class students, average of test result on mathematical creative thinking ability of the experiment class students was better than that average of the control class students, average of self confidence score of the experiment class students was better than that average of the control class students, teacher ability and the learning activities at the experiment class students included in good category, response of the experiment class students to joint the learning is positive.